Athletes versus video game players: A predictive contextual processing study. (25th September 2018) - Diaz-Brage, Pablo; Fernandez-del-Olmo, Miguel; Li, Ling; Rio-Rodriguez, Dan; Fogelson, Noa
Highlights: Comparison of basketball players with video gamers and individual sports athletes. Larger P3b amplitude increases across predictive sequence in basketball players. Increased functional connectivity of frontal networks in basketball and video game players. Abstract: We investigated the effect of abstract and real life meaningful images from sports on predictive contextual processing in professional athletes and video gamers. EEG was recorded in three groups: professional basketball players (BP), professional athletes of individual sports (IA) and experienced action video game players (VG). Two recording sessions, each with a different set of visual stimuli was presented: either triangles facing left, up, right or down or four images of a basketball player throwing a ball. Recording blocks consisted of targets preceded by randomized sequences of standards and by sequences including a predictive sequence signaling the occurrence of a subsequent target event. The gradual increase of P3b amplitudes across the predictive sequence was greater in BP compared with VG, when stimuli consisted of real life images of a basketball player. For the basketball session, we observed increased local modularity and stronger functional connectivity within frontal attentional networks in BP and VG compared with IA, during the processing of the predictive sequence. Our findings suggest increased top-down attentional allocation, during the processing of predictive visual stimuli, in basketball players compared with video gamers and individual sports athletes.